Active case finding strategy for chronic obstructive pulmonary disease with handheld spirometry. Issue 50 (December 2016) - Kim, Joo Kyung; Lee, Chang Min; Park, Ji Young; Kim, Joo Hee; Park, Sung-hoon; Jang, Seung Hun; Jung, Ki-Suck; Yoo, Kwang Ha; Park, Yong Bum; Rhee, Chin Kook; Kim, Deog Kyeom; Hwang, Yong Il
Abstract : Abstract: The early detection and diagnosis of chronic obstructive pulmonary disease (COPD) is critical to providing appropriate and timely treatment. We explored a new active case-finding strategy for COPD using handheld spirometry. We recruited subjects over 40 years of age with a smoking history of more than 10 pack-years who visited a primary clinic complaining of respiratory symptoms. A total of 190 of subjects were enrolled. Medical information was obtained from historical records and physical examination by general practitioners. All subjects had their pulmonary function evaluated using handheld spirometry with a COPD-6 device. Because forced expiratory volume in 6 seconds (FEV6 ) has been suggested as an alternative to FVC, we measured forced expiratory volume in 1 second (FEV1 )/FEV6 for diagnosis of airflow limitation. All subjects were then referred to tertiary referral hospitals to complete a "Could it be COPD?" questionnaire, handheld spiromtery, and conventional spirometry. The results of each instrument were compared to evaluate the efficacy of both handheld spirometry and the questionnaire. COPD was newly diagnosed in 45 (23.7%) patients. According to our receiver-operating characteristic (ROC) curve analysis, sensitivity and specificity were maximal when the FEV1 /FEV6 ratio was less than 77%. The area under the ROC curve was 0.759. The sensitivity, specificity, positive predictive value, and negative predictive value were 72.7%, 77.1%, 50%, and 90%, respectively. The area under the ROC curve of respiratory symptoms listed on the questionnaire ranged from 0.5 to 0.65, which indicates that there is almost no difference compared with the results of handheld spirometry. The present study demonstrated the efficacy of handheld spirometry as an active case-finding tool for COPD in a primary clinical setting. This study suggested that physicians should recommend handheld spirometry for people over the age of 40, who have a smoking history of more than 10 pack-years, regardless of respiratory symptoms. Furthermore, people who have abnormal results, determined using the FEV1 /FEV6 ⩽0.77 cut-off, should be referred for further conventional spirometry to confirm the diagnosis of COPD. However, further studies within the general population are necessary to establish efficacy in the public. Abstract : Supplemental Digital Content is available in the text